Impact of sensory modality and tempo in motor timing - Jeong, Jaeuk; Nam, Soo Mi; Seo, Hyejin (Frontiers in Psychology, 2024)
Background: Accurate motor timing requires the coordinated control of actions in response to external stimuli. Over the past few years, several studies have investigated the effect of sensory input on motor timing; however, the evidence remains conflicting. The purpose of this study was to examine the impact of sensory modality and tempo on the accuracy of timed movements and explore strategies for enhancing motor timing. Methods: Participants (n = 36) performed synchronization and adaptation circle drawing tasks in virtual reality. In Experiment 1, participants synchronized circle drawing with repeated stimuli based on sensory modalities (auditory, visual, tactile, audio-visual, audio-tactile, and visual-tactile) and tempos (20, 30, and 60bpm). Results: A significant interaction effect between modality and tempo was observed in the comparison of timing accuracy. Tactile stimuli exhibited significantly higher timing accuracy at 60bpm, whereas auditory stimuli demonstrated a peak accuracy at 30bpm. In Experiment 2, we examined timing adaptation in circle drawing tasks under conditions of unexpected tempo changes, whether increased or decreased. The analysis revealed a significantly larger timing error when adapting to changes in the tempo-down condition compared with the tempoup condition. Discussion: Through Experiment 1, we found that sensory modality impacts motor timing differently depending on the tempo, with tactile modality being effective at a faster tempo and auditory modality being beneficial at a moderate tempo. Additionally, Experiment 2 revealed that adapting to changes by correcting timing errors is more challenging with decreasing tempo than with increasing tempo. Our findings suggest that motor timing is intricately influenced by sensory modality and tempo variation. Therefore, to enhance the motor timing, a comprehensive understanding of these factors and their applications is imperative.